(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper, PI controller with a simplified decoupled network is developed for controlling the interactive multivariable processes.The controller design is divided into two parts.The first part is designing Relative Gain Array(RGA) matrix in order to measure the amount of interaction among the loops.RGA alsogives a recommendation concerning the most effective pairing of controlled and manipulated variables. The second part is addinga decoupler with PI controller to the control loops to cancel the interaction effects. This proposed design method for multivariable decoupling controller is implemented toMIMO process (Pilot plant).Integral Squared Error (ISE) comparison was carried out to evaluate the performance of the controller. From the ISE analysis conclusions were drawn for the decupled PID controller to be the best performing controller in comparison to PI without decoupler. The controller although complex to understand is very effective in its output performance by providing optimal results.